Lung function decline in asthma: association with inhaled corticosteroids, smoking and sex - Dijkstra, A (BMJ Group, 2006)
BACKGROUND: Inhaled corticosteroids (ICS) provide short term benefits in asthma but the long term effects are still unknown. METHODS: 281 patients diagnosed with moderate to severe asthma in 1963–75 were re‐examined in 1991–9. Information was collected on forced expiratory volume in 1 second (FEV(1)), bronchial hyperresponsiveness, atopy, smoking, use and dosage of oral and ICS. Patients were included in the analyses if they had at least three FEV(1) measurements during two consecutive years after the age of 30 and used ICS during follow up. RESULTS: Analyses were performed on 122 patients. During a median follow up period of 23 years, 71 men and 51 women had on average 37 and 40 individual FEV(1) measurements, respectively. Linear mixed effect models showed that men had a mean annual decline in FEV(1) of 20.6 ml/year less after ICS initiation than before (p = 0.011), and in women the decline in FEV(1) was 3.2 ml/year less (p = 0.73). In individuals with <5 pack years of smoking the decline in FEV(1) was 36.8 ml/year less after ICS institution in men (p = 0.0097) and 0.8 ml/year less in women (p = 0.94), the difference between the sexes being significant (p = 0.045). These effects were not observed in those with ⩾5 pack years smoking. A higher daily dose of ICS was associated with a smaller decline in FEV(1) in men (p = 0.006), an effect not observed in women. CONCLUSION: Treatment with ICS in adult patients with moderate to severe asthma was associated with a reduction in the decline in FEV(1) over a 23 year follow up period in men who had smoked <5 pack years. This effect was dose dependent and was not present in women or in men with ⩾5 pack years of smoking at follow up. The lack of effect of ICS on the decline in FEV(1) in women needs further study.